Development of region-specific soil behavior type index correlations for evaluating liquefaction hazard in Christchurch, New Zealand. Issue 117 (February 2019) - Maurer, B.W.; Green, R.A.; van Ballegooy, S.; Wotherspoon, L.
Abstract: Utilizing an unprecedented database of field and laboratory test data from Christchurch, New Zealand, this study develops deterministic and probabilistic correlations relating the soil behavior type index ( I c ) to laboratory test-based liquefaction susceptibility and fines content. The proposed I c correlations are in turn used to assess liquefaction hazard for 9623 case studies compiled from three earthquakes that impacted Christchurch, New Zealand, wherein the predicted liquefaction severity is compared to post-earthquake field observations. Furthermore, the accuracy of the predictions based on the region-specific I c correlations are compared to those made using generic I c correlations. The use of the Christchurch-specific I c correlations, in general, only slightly improved the liquefaction severity predictions. These findings could be a result of shortcomings in the procedures used to predict liquefaction triggering and/or liquefaction manifestations. Nevertheless, the findings give credence to the use of generic correlations for typical projects. Finally, the overall framework of the study used herein can be applied to worldwide locals and is not just limited for use in the Canterbury region of New Zealand. Highlights: A region-specific I c correlation with liquefaction susceptibility is developed and assessed. A region-specific I c -FC correlation is developed and assessed. The region-specific I c correlations only showed limited improvement in predicted liquefaction severity. For typical projects the use of the generic I c -FC correlation proposed by Boulanger and Idriss (2014) should yield reasonable results.